Factors Affecting Nurse Fatigue During Covid-19 Pandemi (Nurse Case Study in Surakarta) - Musta’in; Dwi Lestari Mukti Palupi; Tri Yuniarti; Erna Kusumawati; Muchamad Syaichul Anam (LPPM Universitas Duta Bangsa Surakarta, 2021)
Currently, cases of people who are indicated and confirmed exposed to Covid-19 have increased higher. One area that has experienced an increase in Covid-19 sufferers is Surakarta. This is a challenge for nurses to be at the forefront of emergency situations for Covid-19 patients. Nurses are part of health workers who are at great risk in efforts to help cure Covid-19 patients. It is feared that the additional duties will make nurses suffer from work. This study aims to see what factors affect the work of nurses in the city of Surakarta. This study uses a descriptive analytic method using primary data sources. Primary data collection was carried out directly by interviewing 30 nurses who worked in the Covid-19 health office in the Surakarta area. Analysis of the data used in this study using the rank spearman. Based on the research results it can be seen that. There is one variable that affects the work of nurses, namely age. This can be seen from the significance value of the variable which is smaller than the alpha value of 0.008. It is feared that the age of having a job with work stress is because older nurses will tire more easily while working, in contrast to younger nurses who usually have better body conditions. Working hours had no effect on the work rate of nurses during the Covid-19 pandemic. This is because nurses get additional working hours due to the return of the patient so that more nursing care must be provided than usual. Work demands also do not affect hard work, especially in this pandemic, although nurses also have to use personal protective equipment, because the workload does not increase the burden on nurses.